Public values to guide childhood vaccination mandates: A report on four Australian community juries - Chris Degeling; Julie Leask; Katie Attwell; Nicholas Wood; Annette Braunack‐Mayer; Kerrie Wiley; Paul Ward; Stacy M. Carter (Wiley, 2024)
Abstract Objective Governments use vaccination mandates, of different degrees of coerciveness, to encourage or require childhood vaccination. We elicited the views of well‐informed community members on the public acceptability of using childhood vaccination mandates in Australia. Methods Four community juries were conducted in Canberra, Launceston, Cairns and Melbourne, Australia between 2021 and 2022. We recruited 51 participants from diverse backgrounds, genders and ages through random digit dialling and social media. Two juries were held in metropolitan areas, and two in regional/rural settings. Outcome measures included jury verdicts and reasons in response to structured questions. Results All juries were concerned about collective protection and individual rights but prioritised the former over the latter. A majority in all juries supported mandates but juries disagreed with respect to the appropriate mandate types. All juries endorsed using the least restrictive or coercive means to encourage vaccination (providing incentives or education, e.g.) before imposing penalties such as financial losses and school exclusions. The overriding view was that it is fairer to place a direct burden on parents rather than children and that mandates should be designed to avoid inequitable impacts on less advantaged groups in society. Many jurors found conscientious objection acceptable as a controlled option for resolute refusers, provided that overall vaccination coverage remains high. Conclusion This paper gives policymakers access to the reasons that Australians have for supporting or opposing different mandates under conditions of high knowledge, understanding and deliberation regarding policy options. Sustaining high rates of vaccination requires high levels of co‐operation between governments, public health actors and the public. Our findings highlight the importance of considering public values in the design and implementation of vaccination mandates. Patient and Public Involvement We sought input from individuals who did and did not vaccinate during the study design. The views and perspectives of nonvaccinating parents were presented in the evidence to juries. We deliberately excluded nonvaccinating individuals from participating, as the divisive and often hostile nature of the topic, and their minority status, made it difficult to ensure they would feel safe as members of the jury without overrepresenting their perspective in the sample. Two related projects engaged directly with these parents.